CAPITAL AND PROFIT-TAKING PERCENTAGE INFLUENCE REVENUE OF GROCERY STORES IN KARANG ANYAR, LANGSA - Aisyah Vania Sitompul (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2021)
This study aims to analyze capital and profit-taking percentage influance on the revenue of grocery stores in Karang Anyar, Langsa. This study uses primary data and the method used to collect primary data is field research methods. The sample selection used Slovin sampling technique. By using Slovin formula, a population of 5 grocery stores and an error limit of 5 percent, obtained a sample of 5 grocery stores. The data analysis technique used to solve problem in the study is multiple linear regression analysis techniques. Based on calculation of Eviews 11, the simultaneous test results show that capital and percentage of profit-taking percentage have a significant effect on the revenue of grocery stores in Karang Anyar, Langsa. Capital and percentage of profit taking partially have a positive and significant effect on the revenue of grocery stores in Karang Anyar, Langsa